Implementasi Kebijakan Penyelenggaraan Angkutan Orang Di Jalan Dengan Kendaraan Umum Sebagai Upaya Mengurangi Kemacetan Di Kota Surabaya Jawa Timur - Robbiatul Adawiyah Awahah; Joko Widodo; Radjikan Radjikan (Birokrasi: JURNAL ILMU HUKUM DAN TATA NEGARA, 2024)
The growth of motorized vehicles is influenced by increased vehicle production and limited public transportation services. The government has launched various models of public transportation to overcome traffic jams in Surabaya due to lack of attention to public transportation. The aim of this research is to find out and analyze the implementation of the policy for organizing people's transportation on the road by public transportation as an effort to reduce congestion in the city of Surabaya and to find out and analyze the factors that influence the implementation of the policy for organizing people's transportation on the road by public transportation as an effort to reduce congestion in the city. Surabaya. This type of research is qualitative research with descriptive methods. The findings from the research results show that in implementing regional regulation policy number 07/2006 concerning public transport on the road, the Surabaya city government has collaborated with transport organizations, operators, public transport owners and the community effectively. The Surabaya government is also increasing the implementation of these policies to achieve the goals of reducing congestion and increasing the efficiency of public transport.